Virtual tool of nonlinear model of interconnected tanks with PID control implementation using EJsS - Oscar Oswaldo Rodríguez-Diaz; Oscar Humberto Sierra-Herrera; Mario Eduardo González-Niño (Dyna)
This paper describes the development and implementation of a virtual tool (TANQUES EN SERIE PID) of a system of two interconnected tanks made in Easy Java/JavaScript Simulations (EJS,), a tool that seeks to motivate learning control concepts in engineering programs. The simulated model corresponds to the non-linear system of interconnected tanks, which presents graphically the behavior of tank levels on an open loop, this application allows varying physical input parameters of the process, as the cross section of the tanks, resistivity constants of the valves and the input flow of process. The system is also presented in closed loop, presenting the behavior when a PID controller is implemented to the process, controller and time constants can be modified to enter a disturbance to the model and by doing this we are verifying the time response and system reaction when subjected to a perturbation. The tool is verified comparing the results using Simulink and equilibrium equations.